Status and distribution of non-volant small mammals in Universiti Putra Malaysia, Bintulu Sarawak Campus (UPMKB) - Musa, Norfahiah; Ibrahim, Azema; Mohd Top, Marina; Mohamed Zakaria (Universiti Putra Malaysia Press, 2012)
This paper presents basic distribution data on non-volant small mammals derived from four sampling periods (2006-2009) in UPMKB. A total of 22 species belonging to families Tupaiidae, Sciuridae, Muridae, Viverridae, Manidae, Tarsiidae, Felidae and Cercopithecidae were captured and recorded. Planted Forest showed the highest number of species (14), followed by Nirwana Forest (11 species), Campus Zone Area (10 species), and Forestry Park (5 species). Two (2) species have been classified as Totally Protected while seven (7) species are protected under the Sarawak Wildlife Protection Ordinance, 1998. Mapping of the total area showed that the Campus Zone Area contained the highest diversity and the number of non-volant small mammals as compared to other sites in UPMKB. Thus, conservation effort of the area should be given higher priority to ensure that the biodiversity of the area is maintained.